Pemanfaatan bungkil biji jarak pagar (Jatropha curcas) terfermentasi sebagai pakan ayam kampung - . Sumiati; Dewi Apri Astuti; Sri Suharti (Jurnal Ilmu Pertanian Indonesia, 2010)
Jatropha curcas"meal (JCM) is very potential as protein source for poultry. The JCM contained high crude protein, i.e. 56,4-63,8% (without hull) and 22,39-31,41% (hulled JCM). JCM serves as a highly nutritious and economic protein supplement in animal feed, if the toxins and antinutrients contained in the JCM are removed. The toxic compounds isolated from jatropha seed include curcin, phorbolesters, and the antinutrients include antitrypsins, tannin, saponin, phytic acid, and high fiber. The objective of this research was to evaluate the effect of feeding fermented JCM on the performances of kampong chickens. In this study, tempeh fungi (fungi using in fermenting soybean) used to ferment the JCM. Two hundred kampung chickens were used in this experiment and reared from day old up to 10 weeks of age. The data analyzed with a Completely Randomized Design with 5 treatment diets and 4 replications, with 10 birds in each replicate. The experimental diets were: TO (the control diet, without Jatropha curcas meal), T1 (the diet contained 5°/o untreated Jatropha curcas meal), T2 (the diet contained 5% fermented Jatropha curcas meal + cellulase 200 ml/ton of feed), T3 (the diet contained 5°/o fermented Jatropha curcas meal + 1000 FTU phytase), and T4 {the diet contained 5% fermented Jatropha curcas meal + cellulase 200 ml/ton + 1000 FTU phytase). The results showed that there were no significant difference on the parameters observed due to the treatments. Feeding fermented Jatropha curcas meal supplemented with cellulase+ phytase{T4) yielded the final body weight and feed conversion ratio similar to those the control {TO) diet. There was no mortality observed in all treatments. Using JCM 5% in the diet is safe for the kampong chickens.